Strategic Training for Future Carreer: The Analysis of Employability Skills of College Students in Cirebon - Agus Umar Akmad; Moh Yudi Mahadianto, (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
In 2030, automation is projected to displace 23 million jobs in Indonesia, while simultaneously creating 27 to 46 million new jobs. Consequently, college students must enhance their employability skills to meet the demands of the evolving job market. This study aims to analyze the employability skills of college students in Cirebon and identify their training needs to prepare for future careers. Utilizing a qualitative research approach with purposive sampling, the findings reveal that college students in Cirebon possess high levels of employability skills, including fundamental skills, teamwork, and personal management skills. Additionally, students recognize the importance of training in soft skills such as communication and negotiation, critical thinking, data visualization, and entrepreneurship to prepare for their careers. The study concludes that a collaborative effort among educational institutions, industries, and the government is essential to implement effective training programs, ensuring that college students become a skilled and adaptable workforce for future career success.